2012
DOI: 10.1177/0884533612445072
|View full text |Cite
|
Sign up to set email alerts
|

Do African American Women Require Fewer Calories to Maintain Weight?

Abstract: Background The high prevalence of obesity in African American (AA) women may result, in part, from a lower resting metabolic rate (RMR) than non-AA women. If true, AA women should require fewer calories than non-AA women to maintain weight. Our objective was to determine in the setting of a controlled feeding study, if AA women required fewer calories than non-AA women to maintain weight. Materials and Methods This analysis includes 206 women (73% AA), aged 22–75 years, who participated in the Dietary Approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
(46 reference statements)
1
2
0
Order By: Relevance
“…Our results are in agreement with several studies carried in the Black African American subject linked to a lower resting metabolic rate [ 111 ]. This study highlight elevated obesity prevalence in the black population [ 112 ].…”
Section: Discussionsupporting
confidence: 94%
“…Our results are in agreement with several studies carried in the Black African American subject linked to a lower resting metabolic rate [ 111 ]. This study highlight elevated obesity prevalence in the black population [ 112 ].…”
Section: Discussionsupporting
confidence: 94%
“…Lower RMR has been hypothesized to be a contributor to increase in obesity prevalence in AA 33,45 . AA women also have been shown to lose less weight despite similar adherence to interventions and it was attributed to lower energy requirements 46,47 . It has been previously shown that lower RMR predicted future weight gain in Pima Indians and pregnant AA women 12,48 .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the implication toward etiology of obesity, lower mRMR has practical ramifications in day-to-day clinical practice in determining daily caloric requirements by the dieticians in individuals who are attempting to lose weight. As the current validated formulas are flawed, some have suggested use of race-specific RMR formulas to improve accuracy of predicative equations 25,51 , but others have concluded that this discrepancy in RMR in AA is not clinically relevant 47,52 . Our study found that AA have a lower daily EE by an average 144 kcal/day compared with Caucasian participants of the same height, weight, age, and gender, and after adjustment for total fat mass and fat-free mass.…”
Section: Discussionmentioning
confidence: 99%